Assessment of iodine nutritional status in school children concerning autoimmune thyroiditis in Tamil Nadu, India - Divya Masilamani; Durai Arasan; Karamath Pyarejan; Seenivasan Venkatasamy; Kumarasamy Kalyanasundaram; Sathya Jeganathan; Athmarthan Krishnasamy; Reji Manjunathan (Indian Journal of Child Health, 2021)
Objective: To eliminate iodine deficiency disorders (IDD) in children, the Indian government implemented a universal salt iodization program more than 3 decades ago. Recently, it was identified that excess iodine intake could lead to autoimmune thyroiditis in children. We aimed to measure the level of iodine excretion as well as thyroid profiles as an option to identify autoimmune thyroiditis in school-going children. Materials and Methods: A total of 111 children between the ages of 6 and 12 years were subjected to a blood test to measure free thyroxine, thyroid-stimulating hormone, anti-thyroglobulin, and anti-thyroperoxidase levels. The children were categorized into control and case groups based on the clinical outcome. Biochemical analysis, thyroid gland assessment, fine-needle aspiration cytology (FNAC), and ultrasound sonography were performed. Urinary iodine excretion (UIE) level was measured by the Sandell-Kolthoff reaction method. Results: Approximately 90% of the study population was identified with a higher level of iodine in urine. A positive correlation was observed between the UIE, anti-TPO, and anti-TGO titers among the cases. Out of 61 cases, 21 children showed overt hypothyroidism (34.43%) and the remaining were identified with subclinical thyroid symptoms (65.57%). FNAC confirmed autoimmune thyroiditis in 43 children within the case group. Conclusion: Excess iodine intake may trigger thyroid autoimmunity in children. Children who are having higher levels of anti-thyroid antibodies are at risk of developing thyroid dysfunction if they consume more than the required iodine for metabolism. High levels of iodine in the urine of control children indicate that the IDD program in our nation is running successfully.